181 Guidelines for the Management of Patients With Spinal Cord Injury: The Optimal Timing of Decompression. (1st August 2016) - Wilson, Jefferson R.; BSc, Lindsay Tetreault; Aarabi, Bizhan; Anderson, Paul A.; Arnold, Paul M.; Brodke, Darrel S.; Burns, Anthony; Chen, Robert; Chiba, Kazuhiro; Dettori, Joseph; Furlan, Julio C.; Harrop, James S.; et al.
Abstract: INTRODUCTION: The objective of this study is to develop guidelines that outline the optimal timing of decompression in patients with traumatic spinal cord injury (SCI) and central cord syndrome. METHODS: A systematic review of the literature was conducted to address the following key questions: (1) What is the efficacy of early decompression (=24 hours) compared with late decompression (>24 hours) based on clinically important change in neurological status? (2) Does timing of decompression influence functional or administrative outcomes? (3) What is the safety profile of early decompression compared with late decompression? (4) What is the evidence that early decompression has differential efficacy or safety in subpopulations? (5) What is the comparative cost-effectiveness of early vs late decompression? A multidisciplinary guideline development group used this information, in combination with their clinical expertise, to develop recommendations for the optimal timing of SCI. The benefits and harms, financial impact, acceptability, feasibility, and patient preferences of each recommendation were carefully considered. RESULTS: The main conclusions from the systematic review included: (1) patients decompressed early were more likely to exhibit clinical improvement in neurological status at 6 months (cervical only) and at discharge from inpatient rehabilitation (all levels); (2) patients treated early for central cord syndrome achieved significantly greater improvements in neurological and functional status than those decompressed late; (3) there were no significant differences in length of acute care/rehabilitation stay or in rates of complications between treatment groups. Our recommendations included: "We suggest that early surgery be considered as a treatment option in adult patients with traumatic central cord syndrome" and "We suggest that early surgery be offered as an option for adult acute SCI patients regardless of level." CONCLUSION: These guidelines should be implemented into clinical practice to improve outcomes and reduce morbidity in patients with SCI by encouraging clinicians to make evidence-informed decisions.